Influence of growth temperature of Escherichia coli on K1 capsular antigen production and resistance to opsonization. - Bortolussi, R (1983)
When Escherichia coli strains that produce K1 capsular polysaccharide antigen at 37 degrees C were grown at 22 degrees C, K1 antigen was not detected in the supernatant or washed-cell fraction of broth cultures. Significant amounts of K1 polysaccharide were detected only when the organism was grown at temperatures of 30 degrees C or higher. Rabbits immunized with an E. coli K1 strain (serotype O18ac:K1:H7) grown at 37 degrees C produced agglutinating antibody to somatic antigen and precipitating and agglutinating antibody to capsular K1 antigen; those immunized with this strain grown at 22 degrees C produced antibody to somatic antigen, but not to K1 antigen. Antibody to somatic antigen was markedly reduced by adsorption with the organism grown at 22 degrees C, while antibody to capsular antigen was not. E. coli K1 strains grown at 37 degrees C (K1 present) resisted phagocytosis and killing if they were opsonized solely by the alternative complement pathway (ACP) using magnesium ethylene glycol-bis(beta-aminoethyl ether)-N,N-tetraacetic acid-chelated serum. When these strains were grown at 22 degrees C (K1 absent), they were opsonized efficiently by the ACP (28 versus 94% killing, respectively; P less than 0.001). In addition, a non-K1 mutant of an E. coli K1 strain was opsonized efficiently by the ACP although its encapsulated K1 parent was not. Sensitivity of E. coli strains to the bactericidal activity of serum was observed in strains with and without K1 capsular antigen. These studies demonstrated that production of K1 polysaccharide antigen was regulated by environmental temperature and that K1 capsule plays an essential role in rendering the organism resistant to opsonization by the ACP.